THIRD GENERATION TELEPHONY: NEW TECHNOLOGICAL SUPPORT FOR COMPUTER ASSISTED LANGUAGE LEARNING - Garcia Cabrero, Jose Carlos (International Journal of English Studies, 2009)
The expansion of the lnternet has Ied to the development of distance teaching models based on the net (e learning). One of the crucial factors in this phenomenon is the continuous training required by workers to maintain or improve their professional skills. Foreign languages are, without doubt, one of the most in demand subjects. This is because they are needed for comunication in an increasingly globalized world. The development of new wireless communication technologies, UMTS or 3G nets, and their corresponding access terminals (Palm-size PCs, PPCs, with wireless telephone connection. also called smart-phones). will enable solutions to be found for some of the problems Iaeed hy current e-learning users. These problems include access speed and the physical constraints of tlhe ( The new wireless comunication technologies will bring other benefits like portability. always on-line, etc.This article presents one on' the world's first prototypes of language learning software or smart-phones, produced by the Laboratorio de lngenieria Didactica e lngenieria Linguistica of UNED (Didactic Engineering and Linguistic Engineering Laboratory) (LIDIL, http://www.vip.~ined.es). i¿le Enl<EDondo.cotn is an lnternet based multimedia application designed for 3G mobile phones with audio, video and interactive exercises for learning Spanish for business.